PENGEMBANGAN PENUNTUN PRAKTIKUM IPA BERBASIS COLLABORATIVE TEAMWORK LEARNING (CTL) UNTUK SISWA SMP NEGERI MEULABOH - Fetro Dola Syamsu (Jurnal Bionatural, 2024)
Teachers at SMPN Meulaboh in carrying out practicum activities have not used practicum guide. The practical activities that teachers do all this time tend to give only instructions. It's because the school doesn't have a practicum guide yet. The difficulties also faced students, because students do not know what practicum activities will be carried out and caused the lack of preparation of students in doing the practicum. The research aims to produce a valid, practical, and effective Collaborative Teamwork Learning practice guide for class VII students at SMPN Meulaboh. Type Development research (Develpomental research), The data gathering techniques used are validation sheet lifts, practicality sheets lift, affective appraisal headings, psychomotor appraisals headings. Techniques of data analysis using descriptive statistics. Validity and practicality tracks are made according to the likert scale. For effectiveness seen through learning outcomes. The overall validity test results obtained a percentage value of 85.20% with valid criteria. The overall teacher practice test results were obtained with a percentage score of 90,86% with very practical criteria. The overall student practicality test results were obtained with a percentage score of 92.65 with highly practical criteria. Testing the effectiveness of the use of IPA Collaborative Teamwork Learning practical guidance obtained through student activity, motivation, and learning outcomesStudents have produced IPA based Collaborative Teamwork Learning practice guides that are effectively used to enhance student's understanding of the concepts and skills of science processes.